2020
DOI: 10.1186/s12863-020-00904-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of transcription factor SlWRKY28 improved the tolerance of Populus davidiana × P. bolleana to alkaline salt stress

Abstract: Background WRKY transcription factors (TFs) have been suggested to play crucial roles in the response to biotic and abiotic stresses. This study is the first to report the alkaline salt regulation of the WRKY gene. Results In this study, we cloned a WRKY gene (SlWRKY28) from the Salix linearistipularis and then transferred to the Populus davidiana × P. bolleana for expression. Sequence analysis on the transcriptome of Salix linearistipular showed the significant up-regulation of WRKY gene expression in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…There are several reports on the resistance functions of the PdpapWRKY28 gene in response to pathogens (Ülker and Somssich, 2004 ; Wu et al, 2011 ), salt stress (Babitha et al, 2013 ; Wang et al, 2020 ), and acids (Chen et al, 2013 ). These studies established a theoretical foundation for our early prediction and subsequent validation experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports on the resistance functions of the PdpapWRKY28 gene in response to pathogens (Ülker and Somssich, 2004 ; Wu et al, 2011 ), salt stress (Babitha et al, 2013 ; Wang et al, 2020 ), and acids (Chen et al, 2013 ). These studies established a theoretical foundation for our early prediction and subsequent validation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Chujo et al ( 2013 ) reported that OsWRKY28 overexpression negatively regulated the innate immune responses of rice against rice blast fungus, resulting in reduced resistance. Wang et al ( 2020 ) reported that overexpression of SlWRKY28 could improve the tolerance of P. davidiana × P. bolleana to alkaline salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…Plants overexpressing SlWRKY28 showed lower H 2 O 2 concentration and significantly higher ascorbate peroxidase (APX) activity comparing to WT. It was speculated that the regulation of enzyme genes in the ROS clearance pathway induced by SlWRKY28 was the potential mechanism for transgenic plants to improve their resistance to alkali and salinity (Wang et al, 2020). SOD plays a leading role in scavenging ROS, which can catalyze the disproportionation of O 2 − free radicals, maintain the balance of reactive oxygen metabolism, protect cell membrane structure from damage, and mitigate the effects of water stress on plants to a certain extent (Das and Roychoudhury, 2014).…”
Section: Physiological Changes Of Plants Overexpressing Mfwrky41 Unde...mentioning
confidence: 99%
“…There are several reports on the resistance functions of the PdpapWRKY28 gene in response to pathogens (Ülker and Somssich, 2004;Wu et al, 2011), salt stress (Babitha et al, 2013;Wang et al, 2020), and acids (Chen et al, 2013). These studies established a theoretical foundation for our early prediction and subsequent validation experiments.…”
Section: Discussionmentioning
confidence: 97%